Allegoric figure of urbs primus in indis - Ghosh, Ayan (2023)
Frederick W. Stevens used allegorical figures to represent concepts like progress and prosperity. This, for example, is a Christian motif of a winged angel holding up a miniature ship to highlight Mumbai's association with maritime trade. The allegoric figure represented is urbs primus in Indis (Latin for the ‘primary urban city of India’), which was adapted as the motto of the Brihanmumbai Municipal Corporation.